2009
DOI: 10.2105/ajph.2008.144279
|View full text |Cite
|
Sign up to set email alerts
|

The Health and Health Care of US Prisoners: Results of a Nationwide Survey

Abstract: Many inmates with a serious chronic physical illness fail to receive care while incarcerated. Among inmates with mental illness, most were off their treatments at the time of arrest. Improvements are needed both in correctional health care and in community mental health services that might prevent crime and incarceration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
536
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 591 publications
(556 citation statements)
references
References 14 publications
12
536
1
7
Order By: Relevance
“…They may be incarcerated for weeks to months and have high rates of illicit substance or alcohol addiction. 1,2,7 Due to chronic infections and the effect of incarceration on health status, 2,5,[8][9][10][11][12] they are a target population for whom availability of antiretroviral (ARV) therapy and general medical care is essential. Introduction and continuation of ARV therapy can be offered while a person is incarcerated, but there are many concerns regarding optimal methods to deliver care in order to maximize personal and public health benefits.…”
mentioning
confidence: 99%
“…They may be incarcerated for weeks to months and have high rates of illicit substance or alcohol addiction. 1,2,7 Due to chronic infections and the effect of incarceration on health status, 2,5,[8][9][10][11][12] they are a target population for whom availability of antiretroviral (ARV) therapy and general medical care is essential. Introduction and continuation of ARV therapy can be offered while a person is incarcerated, but there are many concerns regarding optimal methods to deliver care in order to maximize personal and public health benefits.…”
mentioning
confidence: 99%
“…In contrast to prisons, jails are usually operated by a city, county, parish, or other municipal entity and jail inmates are often awaiting trial or, if already convicted, individuals are almost always serving sentences of less than 1 year. With respect to general health and mental health care, jails and prisons have very different turnover rates and track records of providing timely medical assessment and treatment (Wilper et al, 2009), leading to different opportunities to improve health care in general and palliative care specifically in each setting.…”
Section: Definitions and Methodological Considerations In Reporting Dmentioning
confidence: 99%
“…What we can say is that for some combination of reasons-possibly including inherited predisposition and acquired riskBlacks and Hispanics are at greater risk of developing diabetes, heart disease, high blood pressure and its sequelae (stroke, kidney failure, vascular disease), and Blacks and Asians are at elevated risk of sickle cell disorders (a potential genetic factor). The over-representation of African American and Latino men and women in prison, in combination with the lower educational attainment and SES of the inmate population overall and the harmful synergies between mental health and chronic illness which many inmates experience, yields a population who are sicker than their age-matched free peers (Tanne, 2009;Wilper et al, 2009) One element of lower SES in the United States is the lack of access to health-care services including preventive care, primary care, routine screening and affordable medications. The uninsured and underinsured, the majority of whom are of lower SES, often have to forego medications to treat chronic conditions like diabetes or high blood pressure.…”
Section: Inmate Health Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated a deficiency in the quality of healthcare provided in correctional institutions (Kulkarni, Baldwin, Lightstone, Gelberg, & Diamant, 2010). Consequently, there is an increased prevalence of chronic diseases and mental conditions among prisoners compared to the general U.S. population (Williams, Goodwin, Baillargeon, Ahalt, & Walter, 2012;Wilper et al, 2009). However, few studies have focused on access to care or the state of oral health among incarcerated populations in the U.S., which is an apparent limitation in view of the relationship between oral and general health (Treadwell & Formicola, 2008;Licata & Paradise, 2012).…”
Section: Introductionmentioning
confidence: 99%